ANALISIS BANK SPECIFIC FACTOR TERHADAP PENYALURAN KREDIT PERBANKAN KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Aulya Sukma (2021)
This research includes quantitative research aiming to find out whether there is an influence between capital, credit risk, liquidity, and efficiency towards credit lending. The objects in this research are commercial banks listed on Indonesia Stock Exchange (IDX) with 36 commercial banks choosen as the samples within the period of 2017 - 2019. Research hyptothesis were tested with the significance level of 5%, using panel data regression model and assisted by E-Views 11 program. The result obtained within this research are (1) there is a significant influence between capital and credit lending, (2) credit risk does not significantly influence credit lending, (3) liquidity has significantly influence credit lending, and (4) efficiency does not have any significant influence with credit lending.